2017
DOI: 10.1016/j.otsr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of prolotherapy in the treatment of chronic rotator cuff lesions

Abstract: Level of evidence 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 31 publications
2
84
0
Order By: Relevance
“…Following the title screen, 74 studies were included in abstract screening, of which 24 progressed to full‐text review. A total of 20 studies were removed by the full‐text review, leaving four papers to be included for analysis (Figure ) . One additional article was retrieved through manual reference search of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the title screen, 74 studies were included in abstract screening, of which 24 progressed to full‐text review. A total of 20 studies were removed by the full‐text review, leaving four papers to be included for analysis (Figure ) . One additional article was retrieved through manual reference search of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies were removed by the full-text review, leaving four papers to be included for analysis ( Figure 1). [18][19][20][21][22] One additional article was retrieved through manual reference search of included studies. Authors were in high agreement throughout all stages of screening, with an unweighted kappa of 0.962 for title screening, 0.760 for abstract screening, and 1.00 for full-text screening.…”
Section: Study Characteristics and Demographicsmentioning
confidence: 99%
“…The remaining research is composed mostly of case series. Table 1 presents a list of studies [17‐47] and levels of evidence.…”
Section: Common Regenerative Methodsmentioning
confidence: 99%
“…There is mixed level I evidence for prolotherapy use in rotator cuff tendinopathy. In a 2017 randomized control trial, Seven et al [23] used dextrose prolotherapy in patients with symptoms longer than 6 months' duration and found significant improvements in pain up to a year and significantly improved disability and quality-of-life scores at 6 and 12 weeks and up to 1 year. In addition, this study found significantly greater shoulder abduction, extension, and internal rotation range of motion in the prolotherapy group compared with the physical therapy group; notably, however, there was no difference in external rotation range at any time point [23].…”
Section: Specific Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation